2021
DOI: 10.1186/s12960-021-00628-6
|View full text |Cite
|
Sign up to set email alerts
|

Depression among healthcare workers in the Eastern Mediterranean Region: a systematic review and meta-analysis

Abstract: Background Depression is a major population health challenge globally. This systematic review and meta-analysis aims to (i) determine depression prevalence and (ii) identify the risk and protective factors of depression among healthcare workers (HCWs) in the Eastern Mediterranean Region (EMR). Methods The protocol was registered on Open Science Framework (registration ID: https://osf.io/rdv27). We searched five databases (PubMed, Embase, PsycINFO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 68 publications
(57 reference statements)
0
23
0
2
Order By: Relevance
“…[ 5 7 ] A recent meta-analysis study showed that the prevalence of depression was 33.03% (95% CI: 27.40–29.19%) in healthcare workers in the Eastern Mediterranean Region. [ 8 ] Healthcare workers with depression may negatively affect the quality of their service to their patients, leading to patient dissatisfaction, medical mistakes, and associated financial costs. [ 9 11 ] In some severe cases, patient safety may be compromised.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 7 ] A recent meta-analysis study showed that the prevalence of depression was 33.03% (95% CI: 27.40–29.19%) in healthcare workers in the Eastern Mediterranean Region. [ 8 ] Healthcare workers with depression may negatively affect the quality of their service to their patients, leading to patient dissatisfaction, medical mistakes, and associated financial costs. [ 9 11 ] In some severe cases, patient safety may be compromised.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research findings have demonstrated increased levels of depression, insomnia, anxiety, chronic fatigue, and stress among health care workers during previous epidemics of severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) [6][7][8]. Despite reports of high prevalence of psychological burden pre-COVID-19 pandemic, these front-line responders have been at the epicentre of the global fight against the COVID-19 pandemic with limited resources at their disposal.…”
mentioning
confidence: 99%
“…One of the high-risk groups for poor mental health outcomes globally is healthcare workers (HCWs). More speci cally, studies have shown that they experience high levels of psychological distress and burnout such as depression, anxiety, and poor sleep quality due to their profession [2,3]. This is associated with distressing symptoms such as restlessness, anger, frustration, insomnia and fatigue [2].…”
Section: Introductionmentioning
confidence: 99%
“…This is associated with distressing symptoms such as restlessness, anger, frustration, insomnia and fatigue [2]. In high-income countries in 2015, the prevalence of depression among HCWs ranged from 21.53-32.77%, which was much higher than the global average of 4.4% [3].…”
Section: Introductionmentioning
confidence: 99%